Pharmacoepidemiology and pharmacovigilance : synergistic tools to better Investigate drug safety - Nour, Sabrina (Academic Press, 2019)
Pharmacoepidemiology and Pharmacovigilance: Synergistic Tools to Better Investigate Drug Safety examines the role of pharmacoepidemiologic studies in drug development and its use as a prevention tool in pharmacovigilance activities. The book introduces the various epidemiologic tools and study designs commonly used for the surveillance of drug-related adverse effects and reviews the strengths and weaknesses of each. Criticisms surrounding pharmacoepidemiologic research and issues that often interfere or complicate the conduct and interpretation of these studies are also explored. Case studies illustrate the passive and active surveillance of adverse drug reactions in clinical situations, covering important pharmacoepidemiologic concepts like health risk management and safety. The book helps pharmaceutical industry groups engaged in drug safety, clinical investigators, medical evaluators and those seeking regulatory approval enhance the safety of the drug development process for all patient populations.